PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN NUMERASI SISWA KELAS III SD NEGERI CABEYAN 02 KECAMATAN BENDOSARI KABUPATEN SUKOHARJO - Wahidah Nur Rahmah; Dwi Anggraeni Siwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether there is an influence of the Realistic Mathematics Education (RME) approach on the numeracy ability of third-grade students of SD Negeri Cabeyan 02. This study uses a quantitative method with a quasi-experimental research design, especially with the type of nonequivalent control group design. The population in this study were all third-grade students at SD Negeri Cabeyan 02 and SD Negeri Pohgogor 01, totaling 29 people. The sampling technique used was saturated sampling, where all populations were used as samples. Which resulted in class III of SD Negeri Cabeyan 02 as the experimental class and class III of SD Negeri Puhgogor 01 as the control class. The analysis of this study used the t-test (independent sample t-test), which was previously carried out with the normality test and homogeneity test as a prerequisite test with the help of SPSS version 26. The results showed a Sig. (2-tailed) value of 0.039 < 0.05, which means that the learning process with the Realistic Mathematics Education (RME) approach has an effect on students' numeracy abilities.